Operation smile ; Heroes of Siapo ; Baranggayan [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
A story about a group of Filipino and American doctors who make it a mission to operate on victims of harelip and cleft lip . Magnolia Youth Achievement Awardees set up a livelihood project in Siapo, Tacloban in the middle of a rebel infested community.